2020
DOI: 10.1007/s10342-020-01326-z
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of bark stripping on spruce: the need for red deer population control

Abstract: Norway spruce (Picea abies (L.) Karst.) is a major production tree species for the European wood industry. However, it is highly sensitive to bark stripping (BS) by red deer (Cervus elaphus L.), which causes large timber losses. Because the red deer population has increased over the last decades, a better understanding of the underlying causes driving BS is urgently needed. BS outbreaks are multifactorial: winter food shortage, local and regional deer abundance and stand properties (thermal and visual cover, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 44 publications
(97 reference statements)
0
22
0
Order By: Relevance
“…Although all of these softwood broadleaved species were intensively browsed, Norway spruce and silver birch in the same research stand had almost no browsing damage on their stems (exact data not available). In contrast, many previous authors have observed serious damage on stems of Norway spruce in Central Europe caused by LWH, especially red deer [ 31 , 34 , 35 , 36 ]. These data were likely collected in spruce-dominated stands without significant proportions of attractive broadleaved trees.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Although all of these softwood broadleaved species were intensively browsed, Norway spruce and silver birch in the same research stand had almost no browsing damage on their stems (exact data not available). In contrast, many previous authors have observed serious damage on stems of Norway spruce in Central Europe caused by LWH, especially red deer [ 31 , 34 , 35 , 36 ]. These data were likely collected in spruce-dominated stands without significant proportions of attractive broadleaved trees.…”
Section: Discussionmentioning
confidence: 78%
“…Finally, previous studies have shown that both commercially important and commercially unimportant trees create a suitable environment (e.g., thermal and security cover) and winter/spring forage for LWH [ 15 ]. Thus, addressing the interests of both the forestry and game management sectors requires managing for a sustainable population of LWH that minimizes damage to economically important forest stands [ 35 ] while providing adequate hunting opportunities [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nolte 1999;Honda 2019;Honda et al 2020), because there is no single and 100% effective solution with which to protect from wildlife damage (in a broad sense) (Koehler 1990;Gilsdorf et al 2002). There is consequently a need to identify adequate mitigation measures with which to mitigate HWCs (Redick and Jacobs 2020;Candaele et al 2021). Here, we have assessed the effectiveness of a portable device that was developed by VISEVER S.L.…”
Section: Introductionmentioning
confidence: 99%
“…In relatively large forest areas (over 1000 ha), typical values of annual bark-stripping rates range between 0 and 12% (Candaele et al, 2021). This rate is correlated to deer abundance but the relationship saturates beyond a certain ungulate density (Ligot et al, 2013;Candaele et al, 2021). The other factors that can affect the frequency of bark-stripping damage are winter harshness, forest composition, distance from roads and urban areas, canopy opening, availability of other food resources such as beechnuts and acorns, and topographic position (Ligot et al, 2013;Candaele et al, 2021;Vospernik, 2006).…”
Section: Introductionmentioning
confidence: 99%